The Modalization and Evolution of Human Intellect (Cognitive Systems): Following in the Prophets' Footsteps - Fatemeh Khiveh; Omid Asemani; Sedigheh Ebrahimi; Seyed Ziaeddin Tabei , MD; Farokh Bahram, Sekaleshfar, MD (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Because the sacred texts, encompassing the Qur'an and the Testaments, offer paramount insights into the realization of human excellence and given the Qur'an's authenticity and its complementary nature to preceding scriptures, our study delves into discerning verses from the Qur'an, consulting the perspectives of philosophers and thinkers, and delving into the narratives of divine prophets – who exemplify perfected intellects. The Quran's timeless relevance and universal messages have influenced the development of human intellect across diverse cultures and civilizations. By examining the profound lessons and moral values conveyed through these stories, we can gain a deeper understanding of the perfection of human intellect and its enduring relevance in today's world. Through this exploration, we unveil a sequential progression in the development of human cognition, consisting of distinct phases: Sensory Perception, Apprehension, imaginalization, intellection, and Intuition. As we meticulously examine the accounts of the prophets as recounted from Adam to the seal of prophethood, it becomes evident that these cognitive and intellectual stages have been manifested in the world through these divine messengers. Much like the narratives of the prophets within the Qur'an, human intellects must initially contend with apprehensions, then transition away from their hold, and subsequently engage in a battle against these apprehensions at the opportune moment, triumphing over them. This iterative process enables the intellect to reach its zenith of refinement and perfection, guided by the teachings of the prophets and the constructive, regulatory counsel of these profoundly sanctified and inherently sublime beings, ultimately progressing toward the state of Intuition. The fundamental objective of our inquiry lies in exploring the advancement of human intellect by emulating the archetypal portrayals of the divine prophets found in the Qur'an.